Bleeding Incidence in Patients Administered with Warfarin at Secondary Hospitals in Yogyakarta Province - Vitarani D.A Ningrum; Sufiyah Sufiyah; Irine Dyah Widyastuti; Bacrie Sufriyanto Yusuf; Wahyudin Dullah (Universitas Gadjah Mada, 2020)
Warfarin is an oral anticoagulant most-commonly prescribed for prevention and treatment of thromboembolism. It is widely acknowledged that warfarin has both narrow therapeutic index and various drug-food interactions, thus carrying the risk of subtherapeutic or bleeding. Therefore, warfarin is among the priority drugs to be evaluated to improve the quality of care for warfarin use. This study aimed to analyze the indications and dosage as well as the bleeding incidence in warfarin use at secondary hospitals in Yogyakarta. This research employed the retrospective cross-sectional design among outpatients and inpatients who received warfarin for a minimum of three days. Data of patient demographics, indications and doses of warfarin, incidence of bleeding, and other drugs interacting with warfarin were collected from the medical records for two years of research. The bleeding incidence could include conjunctival bleeding, melena, hematemesis, petechiae, purpura, ecchymosis, or hematochezia as was documented in the medical records. The research involved 139 patients with a majority of male patients and age range of >60 years. The three highest indications of warfarin use were CHF (37.41%), CHF-AF (23.74%), and AF (10.79%) with an average dose of 1.83±0.54 mg/day. Despite the administration of low doses of warfarin, four patients (2.90%) experienced bleeding with hematuria as the main clinical manifestation. This study recommends adjusting to a lower warfarin dose, particularly for the elderly who receive a combination with aspirin. In addition to a lower maintenance dose, a lower therapeutic target of INR should be further verified for Indonesian patients who receive warfarin.